If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 5x + -7 Reorder the terms: 22 = -7 + 5x Solving 22 = -7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 22 + -5x = -7 + 5x + -5x Combine like terms: 5x + -5x = 0 22 + -5x = -7 + 0 22 + -5x = -7 Add '-22' to each side of the equation. 22 + -22 + -5x = -7 + -22 Combine like terms: 22 + -22 = 0 0 + -5x = -7 + -22 -5x = -7 + -22 Combine like terms: -7 + -22 = -29 -5x = -29 Divide each side by '-5'. x = 5.8 Simplifying x = 5.8
| X^2-17x=-30 | | 42=81 | | 24x^2=x^6 | | -2+3(1+2x)=-2x+3 | | 5g-2x=9 | | (-2)(1+6m)=-10+8(10+2m) | | 4(x+5)=10x+5 | | 6v^2-4v-11=-6 | | Y^2-12y=160 | | 0=6-3(5+2x) | | 5p+7=4p+13 | | -3.61=3p+7.7 | | F(x)=2ln(x+3) | | -1+8(7-6x)=2x+6 | | 5g-2x=a | | 3L+12=2L+6L+1 | | 4(a+8)+9=12a-9 | | 9=5-4(2x-5) | | 2(k+1)+9=8k-11 | | 10+9(-10-9x)=8-x | | 2(y-5)-7(y)=-15 | | 3(n+10)+11=7n-1 | | 5(b-1)+3(b-1)=4(3-b)+3(4b-2) | | 6(1-2n)=(-3)(n-2) | | x+x+(4*x)+90=180 | | -2-(4-3x)=-7 | | x+x+(4*x)+90=360 | | (-2x-1/3x)×(-9/7x^3y) | | 5x+2.5x+1=55 | | 6(1-2n)=-3(n-2) | | 8x+10x^2-6=17x | | 1-6(2x-3)=-2 |